Pengaruh Sterilisasi Terhadap Angka Kuman Udara dan Risiko Infeksi Nosokomial di Ruang Operasi Rumah Sakit Nahdlatul Ulama Jombang - Betryana Agnes Pratiwi; Rusmiati Rusmiati; Setiawan Setiawan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
The results of examining the number of germs in the operating room of the Jombang Nahdlatul Ulama House have fulfilled the required requirements of 153 CFU/m3, 145 CFU/m3 and 85 CFU/m3. A high number of germs will provide a great risk for nosocomial infections. The purpose of this study was to study the sterilization instructions for airborne germ rates, with a sample size of 30. The results of this study produced airborne germ before and after the sterilization process, which were 78 CFU m3, 90 CFU/m3, 91 CFU/m3, 71 CFU/m3 and 74 CFU/m3, then after the sterilization process 63 CFU/m3 , 69 CFU/m3, 60 CFU/m3, 64 CFU/m3 and 64 CFU / m3. There was a decrease in numbers from day 1 to day 5 by 15 CFU / m3, 21 CFU/m3, 31 CFU/m3, 7 CFU/m3, 10 CFU/m3. The number of germs in the operating room both before and after did not meet the required quality requirements, but there was a reduction after sterilization. The different test showed a significant difference (α